Profitability Analysis of Dairy Cattle Farming of Village Cooperative Members in Semarang Regency - S. I. Santoso; H. I. Nisa; Mukson Mukson; M. Handayani (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
The study aimed to analyze the profitability of dairy cattle business and the factors that affect the level of profitability of dairy cattle farming at Koperasi Unit Desa (KUD) members in Semarang Regency. The research method used survey method. Samples of KUD were selected by purposive sampling . The selected KUDs were KUD Getasan, KUD Sumber Karya, and KUD Mekar Ungaran. From each KUD, three dairy cow farmer group (KTT) were selected. Ten farmers of each KTT, as samples, were withdrew randomly giving total number of 90 samples. The data were analyzed statistically using descriptive analysis and multiple linear regression model. In this model, the dependent variable was profitability (Y), while the independent variables consisted of the number of lactating cows (x1), the investment value (x2), the milk price (x3), livestock raising experience (x4), milk production (x5), and the cost of concentrate feed (x6). The results showed that the dairy cattle business was profitable and viable. The average profitability of dairy cows was 60.50% and indicating worth to be developed. Multiple regression analysis indicated tha the number of cows (x1), the investment value (x2), the milk price (x3), the livestock raising experience (x4), the milk production (x5), and the cost of feed concentrate (x6) simultaneously had a significant (p<0,01) impact on the profitability of the business. The coefficient of determination (R2) was 0.574 meaning that those factors can explain the level of profitability of 57.40%, and the remaining 42.60% was influenced by other factors outside the model.